Transforming Islamic Philanthropy: Strategies and Impacts of Zakat Institutions in Advancing Social Welfare - Haq, Akiq Zainul; Supriatna, Encup (Hanifiya: Jurnal Studi Agama-Agama, 2026)
Islamic philanthropy through zakat management plays a crucial role in achieving social welfare. This study aims to explore the transformation of zakat management strategies in the Zakat Collection Unit (UPZ) of Pacet Sub-district, Cianjur, and analyze its impact on the local community. Using a descriptive qualitative approach, the study gathered data through in-depth interviews, field observations, and documentation involving UPZ administrators, zakat recipients (mustahik), and other stakeholders. The findings reveal that the UPZ of Pacet Sub-district has implemented various innovations, including the digitalization of zakat collection and distribution systems, as well as enhanced transparency in reporting. These strategies have successfully increased public trust and participation in Islamic philanthropy. The impacts include improved access to education and healthcare services, economic empowerment of zakat recipients, and reduced poverty rates in the area. This study confirms that the transformation of zakat management in the UPZ of Pacet Sub-district significantly contributes to social development. The recommendations proposed include strengthening the capacity of administrators, developing sustainable empowerment programs, and enhancing inter-agency synergy to maximize the benefits of zakat in creating inclusive social welfare.